Retinoic acid, meiosis and germ cell fate in mammals - Bowles, Josephine; Koopman, Peter (Development (Cambridge), 2007)
Although mammalian sex is determined genetically, the sex-specific development of germ cells as sperm or oocytes is initiated by cues provided by the gonadal environment. During embryogenesis, germ cells in an ovary enter meiosis, thereby committing to oogenesis. By contrast, germ cells in a testicular environment do not enter meiosis until puberty. Recent findings indicate that the key to this sex-specific timing of meiosis entry is the presence or absence of the signaling molecule retinoic acid. Although this knowledge clarifies a long-standing mystery in reproductive biology, it also poses many new questions, which we discuss in this review.